Eco Friendly Teaching Aids to Show Parts of a Plant - P. Joshi, Hemali (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Being a Biologist and a Science Educator, studying the leaves of plants is a part of my day to day routine. Having known the fact that photosynthesis takes place in the leaves of the plants, still the leaves are plucked carelessly. Also the flowers which are responsible for pollination and seed formation are tugged off for teaching and study purpose. I have always come up with the teaching aids that add up to the benefits of the Environment. Why not have the teaching aids that are ecofriendly? So, I created some teaching aids that are not only durable but are also creative. Such teaching aids will definitely grab attention of the students. I prepared the slides of different types of leaves to show Venation patterns. These patterns can be easily observed under a dissecting microscope. Similarly, the floral whorls also can be mounted on a slide and preserve for years. These aids need to be precisely prepared in a scientific manner.